Prostate cancer diagnosis by detection of uPM3 in urine - Dr. Kinra Prateek; Dr. B Sivaramakrishna; Dr. Rastogi V (Tropical Journal of Pathology and Microbiology, 2017)
Background: The widespread acceptance of serum PSA testing for the early detection of prostate cancer has been hampered by the low specificity and unnecessary biopsies.Methods: This study was carried out to detect prostate cancers in patients with equivocal PSA values using RT-PCR (Reverse transciptase- polymerase chain reaction) to detect the uPM3 (urinary protein M3) in post prostatic massage urine samples. uPM3 is a mRNA released in prostate cancer patients due to the presence of the oncogene DD3 also called as PCA3 on chromosome 9.Results: There were a total of 27 cases of prostate carcinoma and 33 cases of PIN (prostate intraepithelial neoplasia) detected in this study. The sample collection accuracy depending on presence of beta2 microglobulin (housekeping gene) band was 88%. The sensitivity and specificity of uPM3 keeping histopathology as gold standard was 85.18% and 98.78% respectively. Positive predictive value was 88.46% and negative predictive value was 98.38% which is much higher than PSA. However, no significant correlation of uPM3 positivity was found with Gleason’s grade, metastatic potential and pathological stage.Conclusion: Unlike serum PSA, uPM3 was found to be independent of prostate volume thereby having no false positives unlike raised PSA because of large benign prostate hypertrophy.